The economics of electricity markets - Biggar, Darryl R. (Darryl Ross); Hesamzadeh, Mohammad (Chichester, West Sussex, United Kingdom John Wiley & Sons Ltd, 2014)
"Bridges the knowledge gap between engineering and economics in a complex and evolving deregulated electricity industry, enabling readers to understand, operate, plan and design a modern power system. With an accessible and progressive style written in straight-forward language, this book covers everything an engineer or economist needs to know to understand, operate within, plan and design an effective liberalized electricity industry, thus serving as both a useful teaching text and a valuable reference. The book focuses on principles and theory which are independent of any one market design. It outlines where the theory is not implemented in practice, perhaps due to other over-riding concerns. The book covers the basic modelling of electricity markets, including the impact of uncertainty (an integral part of generation investment decisions and transmission cost-benefit analysis). It draws out the parallels to the Nordpool market (an important point of reference for Europe)"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Electric power consumption; Electric power -- Economic aspects; Electric utilities